Ethical Perception of Tax Evasion: Determinants and Consequences on Voluntary Tax Compliance - Arfah Habib Saragih; I Dewa Nyoman Suartama Putra (Institute of Research and Community Outreach - Petra Christian University, 2021)
This study investigates the factors of ethical perception of tax evasion. We also investigate the effect of ethical perception on tax compliance. Surveys were conducted with 291 participants consist of student, lecturer, professional, and business owner from various backgrounds and majors. Our analysis shows a negative and significant effect of idealism, tax knowledge toward the ethical perception of tax evasion, a positive and significant impact of relativism toward the ethics perception of tax evasion, and no significant effect of religiosity and educational level toward the ethics perception of tax evasion. We found that ethical perception is a significant predictor of voluntary tax compliance.